High Power Quality Three Phase VSI with LCL Filter for Distributed Generation in Microgrid Applications - Pena, Jose Carlos U. [UNESP]; Canesin, Carlos Alberto [UNESP]; IEEE (Ieee, 2016)
The utilization of voltage source inverters with LCL filters is extended in Distributed Energy System. In these applications, the system is controlled as a current source, however, it can also be controlled as a voltage source. Hence, this configuration is suitable for microgrids environment, where the capability to operate in grid connected and islanded modes is required. This paper proposes a strategy to control a three phase voltage source inverter (VSI) with LCL filter with in both operation modes, achieving specific control goals in each mode and smooth transitions between them, even in front of disturbances and variation on system parameters, imposing High Power Quality indices of operation. The proposed strategy is based on a two control loops scheme. Each loop provides a component of the control input (duty cycles) by means of a state-feedback controller. In order to track sinusoidal references with minimum error and to suppress low order harmonics, state vector is expanded to include the states of a resonant controller. Controllers are designed by means of Linear Matrix Inequalities based on discrete time state-space representations of each operation mode, considering uncertainty due to grid impedance. Experimental results of a 4 kW prototype are presented in order to verify the validity of the proposed strategy.
Keywords: Inverter control; islanded operation; linear matrix Inequalities; microgrid inverter; robust control